Refining the history of extreme coastal events in southern Newfoundland, NW Atlantic, with lake sediment archives - Pleskot, Krzysztof; Cwynar, Les C.; Kowalczyk, Cyprian; Kokociński, Mikołaj; Szczuciński, WItold (Elsevier, 2023)
Extreme events, including tsunamis, storm surges and hurricanes, affect the western North Atlantic coast, threatening communities and impacting ecosystems. Although these extreme coastal events (ECEs) are currently thoroughly monitored in the area, older ECEs are known only from short historical evidence. Therefore, establishing a reliable ECE history that extends more than several decades into the past requires data from geological records. This study aims to refine the existing record of ECEs on the southern Burin Peninsula (Newfoundland, Canada) that extends back to the mid-18th century by providing the first lake-sediment-based reconstruction of the event history of the Canadian province of Newfoundland and Labrador. We investigated short sediment cores collected from four shallow coastal lakes. The identification of ECEs relied mainly on lithostratigraphic evidence and peak detection of sand grain counts. Diatoms, dry bulk density, and loss-on-ignition were also analyzed. The age-depth models of the cores were based on 210Pb and 137Cs dating. The correlation of our records with major historical events confirmed that statistically significant sand count peaks, sand layers, and redeposited peat clasts are indicative of major ECEs. We found that the type and characteristics of ECE records depended mainly on the availability of sediment, distance from the seashore, and magnitude of the event. Although some of our ECE markers are associated with marine inundations, only slight diatom community changes were observed, contrary to what is commonly expected from the disturbance of brackish and freshwater ecosystems by major saltwater intrusions. Combined, our records indicate that at least eight ECEs occurred since the late 17th century, three of which might correlate with historically documented events, namely the 1755 CE Lisbon tsunami, the 1775 CE Great Independence Hurricane, and the 1929 CE Newfoundland tsunami. Although further investigations are required to better constrain the type and magnitude of particular ECEs, our study confirms the suitability of geological archives for improving hazard assessment in coastal regions.
Keywords: Newfoundland; tsunami; storm surge; Extratropical storm; Tropical cyclone; Hurricane; Lake sediments; Sand peak analysis; Canada; North Atlantic; coastal lake; extreme event; geohazards; 210Pb; 137Cs; sedimentology; diatoms; age dating; coast; coastal geology; 1929 tsunami; flooding; event deposits; natural hazards; sedimentary record